2009
DOI: 10.1590/s1413-70542009000100016
|View full text |Cite
|
Sign up to set email alerts
|

Precisão experimental em ensaios com a cultura do feijão

Abstract: RESUMOA avaliação do coeficiente de variação (CV) como medida da precisão dos experimentos tem sido feita com diversas culturas, espécies animais e forrageiras por meio de trabalhos sugerindo faixas de classificação dos valores, considerando-se a média, o desvio padrão e a distribuição dos valores de CV das diversas variáveis respostas envolvidas nos experimentos. Neste trabalho, objetivouse estudar a distribuição dos valores de CV de experimentos com a cultura do feijão, propondo faixas que orientem os pesqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
16

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 12 publications
2
25
0
16
Order By: Relevance
“…In the classification of Gomes (2000), a CV of 10% is considered as low, whereas in the present study it is considered very high for feed intake, egg production, eggshell thickness, and specific gravity, and very high for the remaining parameters. This stresses the importance of establishing specific CV classifications, as currently proposed for crops (Clemente & Muniz, 2002;Costa et al, 2002;Carvalho et al, 2003;Lima et al, 2004;Oliveira et al, 2009) and animal production (Judice et al, 1999;Judice et al, 2002;Lana et al, 2006;Mohallem et al, 2008), allowing researchers to verify the accuracy of their own results and of those published in literature.…”
Section: Resultsmentioning
confidence: 94%
“…In the classification of Gomes (2000), a CV of 10% is considered as low, whereas in the present study it is considered very high for feed intake, egg production, eggshell thickness, and specific gravity, and very high for the remaining parameters. This stresses the importance of establishing specific CV classifications, as currently proposed for crops (Clemente & Muniz, 2002;Costa et al, 2002;Carvalho et al, 2003;Lima et al, 2004;Oliveira et al, 2009) and animal production (Judice et al, 1999;Judice et al, 2002;Lana et al, 2006;Mohallem et al, 2008), allowing researchers to verify the accuracy of their own results and of those published in literature.…”
Section: Resultsmentioning
confidence: 94%
“…Likewise, Figure 2 does not show whether the increase in the proportion of coincidence of the 10% selected was due to a reduction in the CV or to an increase in repeatability. Oliveira et al (2009), evaluated the influence of CV on the experimental accuracy in common bean and concluded that CV is different among variables, since each variable has different genetic parameters, such as genetic variance and heritability, and consequently the experimental accuracy is different.…”
Section: Resultsmentioning
confidence: 99%
“…Oliveira et al (2009) studied the distribution of CV values of common bean crops and proposed ranges that guide researchers in the experiment evaluation. To this, the authors calculated the CV ranges for yield, number of pods per plant, number of grains per pod, 100-grain weight, final stand, plant height, and harvest index.…”
Section: Introductionmentioning
confidence: 99%
“…Os ensaios com CVe alto e muito alto são preocupantes. Assim, segundo os três critérios de classificação dos CVe da produtividade de grãos de feijão (OLIVEIRA et al, 2009), apenas os ensaios 4 e 6 tem CVe alto e muito alto.…”
Section: Resultsunclassified